Out of order Homosexuality in the Bible and the ancient near east - Wold, Donald J. (Grand Rapids, MI Baker, 1998)
Includes bibliographical references and indexes.
Keywords: Homosexuality in the Bible; Homosexuality -- religious aspects -- Christianity; Homosexuality -- Biblical teaching